Zmiany powierzchni leśnych na terenie Parku Krajobrazowego Puszcza Zielonka w ostatnich 180 latach w aspekcie krajobrazowym - Macias, Andrzej; Bródka, Sylwia; Kubacka, Marta (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2023)
The article presents the results of research on changes in forest areas in the PuszczaZielonka Landscape Park. An analysis of forest area transformations was carried out with the use of landscape metrics. Archival cartographic material in the form of topographic maps in the scale of 1 : 25 000, coming from four different periods (1830, 1890, 1940 and 1979/80) and a generalized Database of Topographic Object (BDOT) dated 2010, were used for the research. The result of the research are quantitative and qualitative characteristics of changes in the area and the spatial layout of the forest areas and a model of landscape processes taking place in the Puszcza Zielonka Landscape Park. The first analyzed period (1830–1890) was characterized by a small regression of forest area (index of changes WD = ‒0.05), whereas fragmentation and dissection of forest patches prevailed. The second period (1890–1940), despite the slight increase in forest areas (WD = +0.03), was characterized by a decrease in the number of patches and a reduction of their borders’ length. In the third period (1940-1979), the landscape increment process (WD = +0.27), mainly related to the filling of non-forested areas within forest complexes, prevailed. After 1979, the direction of changes was similar but on a much smaller scale (WD = +0.04).